Audience Perception of Media Reporting of Separatist and Sectarian Agitations in Nigeria - Joseph Oluchukwu Wogu; Patrick Egwu (Cхід, 2019)
For some time now, Nigeria has faced the threat of secession from different groups. Each of the groups feels that the country is not representing their interest. In particular, most of the groups feel that the interest of their people has not been properly represented in terms of power sharing. Nigeria operates a democratic system of government with three tiers namely the executive, the judiciary and the legislature. The country also has six geo-political zones for the purposes of power sharing. The zones are North East, North West North, North Central South East, South West and South-South. The 36 states of the federation are, therefore, groups into the various zones with unequal number of states. For example, the North East has six states, the North West has seven, the North Central has six the same as South-South and South-West. However, the South-East has only five states. The unequal number of states among the geo-political zones has serious implications for power sharing in the country. For example, each state has three elected senators and a number of house of representative members depending on the population of the state. What this means is that the South-East has less number of senators and House of Representative members. Their counterparts from North-West is likely is likely to have the highest number of representatives. Zones like North Central, North East, South-West and South-South will have equal number of Senators but the number of House of Representatives may differ depending on the population. This unequal representation could have implications on the promotion of bills and policies and motions in the National Assembly that address issues that affect the welfare of each of the people of each geo-political zones. The mere thinking that South-East is outnumbered in the National Assembly could also make people of the zone to view almost every government programme and policy with suspicion. People of the area may be thinking that the government at the centre does not represent their interest. They may also be thinking that the country does not mean well for them. All these could provide fertile ground for agitations to fester. This partly explains why the country has faced agitations from people from South-East who have over the years sought to separate from Nigeria. Such agitations have also been reported in the media. This paper investigates audience perception of this reporting. The study sought answers to four research questions. Survey research was adopted for the study. A total of 384 respondents were recruited for the study. The questionnaire was the instrument for data collection. The data generated were analysed using both descriptive and inferential statistics. It was found that most of the respondents studied reported high frequency of exposure to media reports on secession agitations. The result also showed that the media of exposure were radio, TV, and newspapers. The sample studied perceived media reports on secession agitations as supporting such actions. The result also showed a significant relationship between exposure to media reports on secession and public perception. The researchers recommend, among others, that the Nigerian Union of journalists should step up their monitoring mechanism to ensure that media reports do not compromise national unity.